Stereoacuity test as a screening tool for amblyopia and binocular vision in children 6-12 years of age - Surasmiati, Ni Made Ayu; Wetarini , Krisnhaliani; Wijayati , Made Paramita; Suryathi, Ni Made Ari (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundStereoacuity is essential for depth perception and daily activities, complementing visual acuity. Assessing stereoacuity in children is vital for detecting binocular vision disorders and amblyopia. This study aimed to compare the Toegepast Natuurwetenschappelijk Onderzoek (TNO) test and the Titmus Fly test in school-based vision screening for children aged 6-12 years. MethodsA cross-sectional study was conducted in social service settings with 122 elementary school children aged 6-12 years. Examinations included visual acuity, refraction, Ishihara color vision, and stereoacuity using both the TNO and Titmus Fly tests. Statistical comparisons were made using the Wilcoxon Signed-Ranks Test, and stereoacuity differences based on demographic factors and visual acuity were assessed using the Mann-Whitney U Test. The level of agreement between the two tests was determined using Bland-Altman analyses. Results Visual acuity significantly influenced stereoacuity results in the Titmus Fly test (p=0.001), with children having abnormal visual acuity performing worse. Approximately 68% of children reported that the Titmus Fly test was easier to perform. The mean difference between TNO and Titmus Fly measurements was 79.52 ± 63.75 (95% CI = 68.14–90.90; p=0.001), demonstrating a consistent bias between the two tests. Conclusion The Titmus Fly test is easier for children (6–12 years) to perform, but it tends to overestimate stereoacuity values compared to the TNO test, making the two methods non-interchangeable and not reliable. Stereoacuity assessment remains essential in school-based vision screening for evaluating binocular vision and amblyopia, especially in children with refractive errors.